Effect of Massage on treatment of preterm feeding intolerance: Study protocol for a randomized controlled trial - Nan Peng; Lizhen Fu; Rui Li; Xiaohua Liang; Qi Lu (Wiley, 2023)
Abstract Aim To evaluate the effectiveness of massage on treating feeding intolerance (FI). Design A randomized, controlled, prospective clinical trial. Methods A total of 104 preterm infants whose gestational age between 28 and 34 weeks and birth weight between 1000 and 2000 g with diagnosis of FI were recruited. Participants were stratified by birth weight (1000-1499 g or 1500-2000 g) and randomized to either the intervention group, who will receive 7 days of massage, or the control group. The primary outcome is the time to reach full enteral nutrition. Secondary outcomes include duration of FI, change of body index, length of hospitalization, change of gastric residual volume, abdomen circumference and defecation measurement before and after 7 days of intervention. Results Results of this study, which includes index on FI and physical development, have the potential to provide evidence that massage will alleviate symptoms of FI, and contribute to the long‐term positive outcome of preterm infants.